An Ethereum-based implementation of English, Dutch and First-price sealed-bid auctions - Pop, Claudia; Prata, Mirela; Antal, Marcel; Cioara, Tudor; Anghel, Ionut; Salomie, Ioan (2020 IEEE 16th International Conference on Intelligent Computer Communication and Processing (ICCP), 2020)
This paper addresses the problem of the traditional online auctions by proposing an Ethereum based implementation for three of the most popular auctions: English, Dutch, First-price sealed-bid (FPSB). Such centralized systems are subjects to malicious attacks, unreliable third-party for payment module or repudiation of bids. We present a set of properties that advantages a blockchain auction, which tackles the drawbacks of a traditional one. Furthermore, we define smart contracts for expressing the auctions based on strict rules regarding the role of the participants and stage delimitation. While English and Dutch auction have a public character, the sealed bids from a FPSB can be questioned. The proposed solution incorporates the Merkle proof algorithm for honest verification of these offers. The experimental results show that a Dutch auction is more suitable for sellers, while an English auction for bidders in terms of transaction fees. Based on the behavior of each type of auction, the solution is exemplified by an English auction in the real-estate field, including a protocol for storing data off-chain.